Pengaruh Insentif Manajemen dan Corporate Governance terhadap Corporate Fraud - Nahdiatul Ummah; Suwarno Suwarno (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to examine the effect of management incentives and corporate governance on corporate fraud. The data source used in this study is secondary data in the form of company annual reports obtained from the official website of the Indonesia Stock Exchange. The sample in this study was 104 data from food and beverage subsector manufacturing companies in 2019-2022 using purposive sampling technique. The data analysis technique used in this study used the SmartPLS 3.2.9 program. The results of this study indicate that management incentives have no effect on financial statement fraud, independent commissioners have no effect on financial statement fraud, audit committees have no effect on financial statement fraud and institutional ownership have no effect on financial statement fraud.